Penerapan Sistem Basis Data Pada Minimarket Alfamart - M.Raihan; Muhammad Irwan Fadli Nasution (Journal of Management and Creative Business, 2023)
In Indonesia, Alfamart is a large supermarket chain with many locations. In 1989, Djoko Susanto and his family launched the Alfamart supermarket chain. Originally known as PT Sumber Alfaria Trijaya Tbk (the Company), branched out into wholesale and retail in 1999. The company started exponential growth in 2002 by purchasing 141 Alfa Minimart locations and changing its name to Alfamart. Alfamart's vision is to establish itself as a superior community owned retail distribution network dedicated to driving small business growth, exceeding customer expectations, and remaining competitive on a global scale. The modern retail industry can take advantage of Indonesia's consumption of IDR 3,600 trillion in 2016.